Evidence-based practice in nursing & healthcare : a guide to best practice - Melnyk, Bernadette Mazurek (Wolters Kluwer, 2019)
Evidence-Based Practice in Nursing & Healthcare: A Guide to Best Practice, 4th Edition Bernadette Mazurek Melnyk, PhD, RN, APRN-CNP, FAANP, FNAP, FAAN and Ellen Fineout-Overholt, PhD, RN, FNAP, FAAN